Microbial diversity and community structure in Fynbos soil - ETIENNE SLABBERT; RAPHAEL Y. KONGOR; KAREN J. ESLER; KARIN JACOBS (Molecular Ecology, 2010)
The Fynbos biome in South Africa is renowned for its high plant diversity and the conservation of this area is particularly important for the region. This is especially true in the case of endangered vegetation types on the lowlands such as Sand Fynbos, of which only small fragments remain. The question is thus whether the diversity of the above‐ground flora is mirrored in the below‐ground microbial communities. In order to determine the relationship of the above‐ and below‐ground communities, the soil community composition of both fungal and bacterial groups in Sand Fynbos was characterized over space and time. A molecular approach was used based on the isolation of total soil genomic DNA and automated ribosomal intergenic spacer analysis of bacterial and fungal communities. Soil from four different sites was compared to resolve the microbial diversity of eubacterial and fungal groups on a local (alpha diversity) scale as well as a landscape scale (beta diversity). The community structures from different sites were compared and found to exhibit strong spatial patterns which remained stable over time. The plant community data were compared with the fungal and the bacterial communities. We concluded that the microbial communities in the Sand Fynbos are highly diverse and closely linked to the above‐ground floral communities.